Tính nhanh:
a) -37 + 54 +(-70) +(-163) + 246;
b) -359 +181+(-123)+ 350+(-172);
c) -69+53+ 46+(-94)+(-14)+ 78;
d)13-12+ 11+10 – 9+ 8– 7– 6+5– 4+3+ 2– 1
Tính nhanh:
a) -37 +54 +(- 70)+(- 163)+246
b)-359 +181+(-123)+350+(-172)
c)-69 +53 + 46 +(- 94)+(- 14) + 78
d)13 -12 +11 +10 -9 + 8 -7 -6 +5 - 4 +3 +2 -1
a: =17-70-163+246
=-43-163+246
=246-206
=40
Tính nhanh - 37 + 54 + -70 + -163 + 246
-37 + 54 + (-70) + (-163 ) + 246
= [ (-37) + (-163) ] + ( 54 + 246 ) + (-70)
= -200 + 300 + (-70)
= 100 + (-70)
= 30
dap an cua Den do
-37+54+(-70)+ (-163)+246=?
\(-37+54+\left(-70\right)+\left(-163\right)+246\\ =-37+54-70-163+246\\ =\left(-37-163\right)+\left(54+246\right)-70\\ =-200+300-70\\ =100-70\\ =30.\)
(-37)+54+(-70)+(-163)+246
(-37)+54+(-70)+(-163)+246
=[(-37)+(-163)]+(54+246)+(-70)
=[-(37+163)]+300+(-70)
=-200+300+(-70)
=[+(300-200)]+(-70)
=100+(-70)
=+(100-70)
=30
Tính NHANH
a. -37 + 54 + (-70) + (-163) + 246
Tính nhanh
-37+54-70-163+246
= -(37+163)+(54+246)-70
= -200+300-70
= 100-70=30
Tính nhanh
-37+54-70-163+246
= (-37-163) + (54+246) - 70
= [ -37 + (-163)] + 300 -70
= [-(163+37)] + 300 - 70
= -200 + 300 - 70
= + (300-200) - 70
= 100 - 70
= 30
-37 + 54 - 70 - 163 + 246
= [(246 + 54) + (-37 - 163)] - 70
= [300 + (-200)] - 70
= 100 - 70
= 30
tính nhanh
-37+54+(-70)+(-163)+246
-37+54+(-70)+(-163)+246
= - 37 + 54 - 70 - 163 + 246
= (-37 - 163) + ( 54 + 246) - 70
= -200 + 300 - 70
= 100 - 70
= 30
Tính nhanh
a, -37 + 54 + (-70) + (-163) + 246
b, -359 + 181 + (-123) + 350 + (-172)
a)(-37)+54+(-70)+(-163)+246
=[(-37)+(-163)]+(54+246)+(-70)
=(-200)+300+(-70)
=[(-200+(-70)]+300
=(-270)+300
=30
b)(-359)+181+(-123)+350+(-17)
=[(-359)+(-123)+(-17)]+[181+350]
=(-499)+531
=32
tick cho mk nha bạn
\(\left(-37\right)+54+\left(-70\right)+\left(-163\right)+246\)
= \(-37+54-70-163+246\)
\(=\left(-37-163\right)+\left(54+24\right)-70\)
\(=-200+78-70\)
\(=-200+\left(78-70\right)\)
\(=-200+8\)
\(=-192\)
Tính nhanh nếu có thể ( áp dụng quy tắc dấu ngoặc )
a, (125 - 679 + 145) - (125 - 679)
b, -37 + 54 + (-70) + (-163) + 246
a) (125 - 679 + 145) - (125 - 679)
= 125 - 679 + 145 - 125 + 679
= ( 125 - 125) - (679 - 679) + 145
= 0 - 0 + 145
= 145
a, (125 - 679 + 145) - (125 - 679)
125-679+145-125+679
=(125-125)+(-679+679)+145
=0+0+145
=145
b, -37 + 54 + (-70) + (-163) + 246
=[-37+(-70)+(-163)]+(54+246)
=[-107+(-163)]+300
=-270+300
=30
Trả lời:
\(a,\)\(\left(125-679+145\right)-\left(125-679\right)\)
\(=125-679+145-125+679\)
\(=\left(125-125\right)-\left(679-679\right)+145\)
\(=0-0+145\)
\(=145\)
\(b,\)\(-37+54+\left(-70\right)+\left(-163\right)+246\)
\(=\left(-37-163\right)+\left(54+246\right)-70\)
\(=-200+300-70\)
\(=100-70\)
\(=30\)
Hok tốt!
Vuong Dong Yet